METHODS OF EARLY CHILDHOOD CHARACTER EDUCATION: A STUDY OF MUHAMMAD ‘ATHIYAH ABRASYI’S IDEAS - Euis Cici Nurunnisa (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study seeks to explore the ideas of Muhammad ‘Athiyah Al-Abrasyi about the method of character education for early childhood. It is believed that this study would help identify an early childhood technique of moral or character education that is suitable and pertinent for character education in the nation's educational institutions. According to Muhammad 'Athiyah Al-Abrasyi's, the core of Islamic education is moral teaching for young children. Early moral education should serve as the cornerstone of Islamic education. The Qur'anic principles or teachings serve as the foundation for early moral instruction. He claims that the goal of moral education in Islam is to create individuals with high moral standards, a strong sense of self, etiquette in speech and decency in behavior, as well as a mature, civilized, sincere, honest, and religious temperament. Al-Abrasyi devised a number of methods for instilling moral values in young children, including: (1) the direct method, which involves giving instructions, guidance, and advice while pointing out the advantages and drawbacks of something; (2) the indirect method, which involves suggesting or providing children with encouragement, strength, trust, and inner memories; and (3) the method by capitalizing on children's propensities and tendencies to imitate their parents.